Microbiological flora of cell phones: a reservoir of potential pathogens? - Kanishtha Sharma; Dipender Kaur Najotra; Poonam Slathia; Shivani Raina (International Journal of Medical Research and Review, 2017)
Background: Hospital associated infections are a major problem in all hospital settings. The heavy use of cell phones which come in close contact with the body surfaces could act as a fomite for microorganisms and it can transmit pathogenic as well as non pathogenic microorganisms.Objective: To determine the rate of bacterial contamination of cell phones of hospital staff and to study their antibiogram.Methods: A cross-sectional study was conducted in a tertiary care hospital. Sterile swabs were collected from cell phone surfaces of healthcare workers (HCW). The samples were processed as per standard microbiological techniques and antimicrobial susceptibility testing was done.Results: Out of the 100 cell phones studied, 60(60%) showed bacterial growth. 28(56%) were from doctors and 32(64%) from the paramedical staff. Staphylococcus aureus with 37(55.23%) isolates was predominant followed by CONS 12(17.93%), Pseudomonas sp. 7(10.44%), E. coli 4(5.97%) and Klebsiella pneumoniae 3(4.47%), 2(2.98%) Acinetobacter sp and Bacillus sp. 36 of HCW had cleaned their cell phones out of which 16 (44.44%) showed bacterial growth whereas 64 cell phones had never been cleaned, out of which 44 (68.75%) showed bacterial growth. Among the Gram positive isolates, Linezolid and Vancomycin were the most effective antibiotics and Imipenem and Piperacillin-Tazobactam were most effective against Gram negative isolates.Conclusion: HCW are exposed to pathogenic microorganisms which can be easily transferred to their cell phones thus acting as a source of infection to others. Cleaning of cellphones with alcohol based disinfectants and frequent hand washing should be encouraged.